2012
DOI: 10.1038/onc.2012.390
|View full text |Cite
|
Sign up to set email alerts
|

EZH2 promotes a bi-lineage identity in basal-like breast cancer cells

Abstract: The mechanisms regulating breast cancer differentiation state are poorly understood. Of particular interest are molecular regulators controlling the highly aggressive and poorly differentiated traits of basal-like breast carcinomas. Here we show that the Polycomb factor EZH2 maintains the differentiation state of basal-like breast cancer cells, and promotes the expression of progenitorassociated and basal-lineage genes. Specifically, EZH2 regulates the composition of basal-like breast cancer cell populations b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 44 publications
5
38
0
Order By: Relevance
“…This analysis revealed that regions bound by EZH2 exclusively in MMSET-low TKO cells coincided with GATA3, HOXA2 and PDX1 motifs (Figure 4E). In breast cancer cells, GATA3 and EZH2 are functionally antagonistic, suggesting that similar interplay between these two factors may also exist in myeloma [38]. Interestingly, EZH2-bound regions specific to MMSET-high NTKO cells were associated with DNA motifs that resemble known CTCF DNA binding sites (Figure 4E), implying a possible mechanism where insulator sequences may protect these loci from methylation by MMSET.…”
Section: Resultsmentioning
confidence: 98%
“…This analysis revealed that regions bound by EZH2 exclusively in MMSET-low TKO cells coincided with GATA3, HOXA2 and PDX1 motifs (Figure 4E). In breast cancer cells, GATA3 and EZH2 are functionally antagonistic, suggesting that similar interplay between these two factors may also exist in myeloma [38]. Interestingly, EZH2-bound regions specific to MMSET-high NTKO cells were associated with DNA motifs that resemble known CTCF DNA binding sites (Figure 4E), implying a possible mechanism where insulator sequences may protect these loci from methylation by MMSET.…”
Section: Resultsmentioning
confidence: 98%
“…By contrast, GATA3, a driver of luminal differentiation, performs an opposite function to that of EZH2, suppressing bi-lineage identity and luminal-progenitor genes expression. Indeed, GATA3 levels increase upon EZH2 silencing, mediating a decrease in bi-lineage cell numbers (Granit et al 2012). Interestingly, the three genes with the greatest negative correlation with VGLL1 and miR-934 in the TCGA dataset were GATA3, ESR1, and FOXA1, which form a functional enhanceosome that regulates the genes driving core ERa functions and that co-operatively modulates the transcriptional networks previously ascribed to ERa alone (Kong et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, EZH2 was shown to promote a bi-lineage identity in basal-like breast cancer cells (Granit et al 2012), and luminal progenitor-associated genes, including VGLL1, were preferentially downregulated in EZH2-silenced cells and upregulated in EZH2-overexpressing cells. By contrast, GATA3, a driver of luminal differentiation, performs an opposite function to that of EZH2, suppressing bi-lineage identity and luminal-progenitor genes expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enhancer of zeste (EZH)2, a methyltransferase component of polycomb repressive complex 2(PRC2) has been found deregulated in many sorts of cancers, including lymphoma [148,149], bladder [150][151][152][153], gastric [154,155], lung [156], breast cancers [157][158][159]. EZH2 catalyzes H3K27me3 in the presence of suppressor of zeste 12 (SUZ12) and embryonic ectoderm development (EED) which possess a carboxy-terminal domain specifically recognizes histone tails that carry trimethyl-lysine residues [160].…”
Section: Histone Associated Protein Deregulation In Cancer and Epigenmentioning
confidence: 99%